2020
DOI: 10.1177/1538574420952923
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in Peripheral Vascular Disease: Endovascular Revascularization as a Potential Therapeutic Target

Abstract: Introduction: Erectile dysfunction (ED) affects more than 150 million men worldwide, with deleterious effects on quality of life. ED is known to be associated with ischemic heart disease but the impact of ED in patients with peripheral arterial disease (PAD) is unknown. We assessed the prevalence and severity of ED in patients with PVD. Methods: Following ethical approval, sequential male patients diagnosed with PAD over a 1-year period following diagnosis of intermittent claudication. The patient demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although erection is a complex neurovascular process involving the participation of the vascular endothelium, autonomic nerves, smooth muscle and extracellular matrix, as a vascular event, intact endothelium is essential (Gratzke et al., 2010). ED was found to be common in patients with diabetes and disseminated vascular diseases such as peripheral atherosclerosis and coronary, because most of these patients cannot maintain intact endothelium (Benaragama et al., 2020; Kouidrat et al., 2017). ED is also currently considered to be an early indicator of endothelial dysfunction and cardiovascular disease (Mostafaei et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although erection is a complex neurovascular process involving the participation of the vascular endothelium, autonomic nerves, smooth muscle and extracellular matrix, as a vascular event, intact endothelium is essential (Gratzke et al., 2010). ED was found to be common in patients with diabetes and disseminated vascular diseases such as peripheral atherosclerosis and coronary, because most of these patients cannot maintain intact endothelium (Benaragama et al., 2020; Kouidrat et al., 2017). ED is also currently considered to be an early indicator of endothelial dysfunction and cardiovascular disease (Mostafaei et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, younger patients felt more severe limitations in terms of the social relationships caused by PAD as with age, and due to other comorbidities, older people tend to become used to being limited in their social lives. Intimate relationships were the least affected area of life, irrespective of age or disease severity, the majority of our patients reported as having been satisfied with this aspect of their lives, which underlines the importance of the support coming from close relationships with family and friends in coping with a progressive medical condition, especially as positive adaptation showed a considerable decrease in older patients in our study, and worse perceived health status has been shown to be associated with deteriorating mental health [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 63%
“…As mentioned above, ED is recognized as a vascular disease. In fact, various vascular diseases, such as atherosclerosis, coronary heart disease, and peripheral artery disease, are known to cause ED because endothelial damage and subsequent atherosclerotic plaque formation are common etiologies of ED and other vascular diseases [ 24 , 25 ]. Lipid metabolism abnormalities and monocyte/macrophage activity are reported to be crucial factors in the relevant pathological steps, including atherosclerotic plaque formation [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Vasculogenic Erectile Dysfunctionmentioning
confidence: 99%